2014
DOI: 10.1002/biot.201300553
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, magnesium, and calcium ion supplementation confers tolerance to acetic acid stress in industrial Saccharomyces cerevisiae utilizing xylose

Abstract: Lignocellulosic biomass is a potential substrate for ethanol production. However, pretreatment of lignocellulosic materials produces inhibitory compounds such as acetic acid, which negatively affect ethanol production by Saccharomyces cerevisiae. Supplementation of the medium with three metal ions (Zn(2+) , Mg(2+) , and Ca(2+) ) increased the tolerance of S. cerevisiae toward acetic acid compared to the absence of the ions. Ethanol production from xylose was most improved (by 34%) when the medium was supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The supplementation of the growth medium with zinc sulfate also improved S. cerevisiae tolerance to acetic acid, with zinc presumably acting as an anti-oxidative agent ( Wan et al, 2015 ). The addition of zinc and other metal ions (Mg 2+ and Ca 2+ ) was also associated to an increase of S. cerevisiae tolerance toward acetic acid ( Ismail et al, 2014 ). The comparison of the transcriptional profiling of cultures supplemented or not with each of the three metal ions and acetic acid suggested that these ions are involved in the regulation of different genes, and that the up-regulation of cell wall and membrane genes is related with the increased tolerance to acetic acid upon metal ion supplementation ( Ismail et al, 2014 ).…”
Section: Physiological Genomics-guided Strategies To Improve Acetic Amentioning
confidence: 99%
“…The supplementation of the growth medium with zinc sulfate also improved S. cerevisiae tolerance to acetic acid, with zinc presumably acting as an anti-oxidative agent ( Wan et al, 2015 ). The addition of zinc and other metal ions (Mg 2+ and Ca 2+ ) was also associated to an increase of S. cerevisiae tolerance toward acetic acid ( Ismail et al, 2014 ). The comparison of the transcriptional profiling of cultures supplemented or not with each of the three metal ions and acetic acid suggested that these ions are involved in the regulation of different genes, and that the up-regulation of cell wall and membrane genes is related with the increased tolerance to acetic acid upon metal ion supplementation ( Ismail et al, 2014 ).…”
Section: Physiological Genomics-guided Strategies To Improve Acetic Amentioning
confidence: 99%
“…Although the relationships between these genes and tolerances to fermentation inhibitors and high temperature have not been reported, this result suggests that intracellular pools of metal ions are involved in the multiple stress tolerances of Hyb-8. Ismail et al ( 2014 ) reported that supplementation of three metal ions (Zn 2+ , Mg 2+ , and Ca 2+ ) increased the tolerance of S. cerevisiae toward acetic acid stress. In addition, Bellí et al ( 2004 ) reported that a group of genes implicated in metal ion homeostasis, including TIS11, SIT1 , and FTR1 , was induced in Δ grx5 cells, which are models for studying the influence of continuous oxidative stress on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kosaka et al (2020) investigated the effect of different metal ions on the thermotolerance of Z. mobilis TISTR548 and related mutants, and demonstrated that the addition of Mg 2+ and K + reduced intracellular reactive oxygen species (ROS) accumulation at critical high temperature (CHT) with an increase of CHT by 1 • C, which is probably due to the stabilization of both outer and inner membranes as well as the maintenance of homeostasis for cellular metabolism by the addition of Mg 2+ and K + . In addition, the effect of supplementation of zinc on the ethanol fermentation performance of the self-flocculating yeast in the continuous ethanol fermentation was studied (Zhao et al, 2009;Xue et al, 2010;Ismail et al, 2014), and the roles of zinc and zinc containing proteins in yeast metabolism and cellular stress responses were summarized (Zhao and Bai, 2012).…”
Section: Introductionmentioning
confidence: 99%